Tata Hijau pada Ruang Jalan Menuju Kenyamanan Termal Iklim Mikro Studi Kasus: Jalur Pedestrian, Penggal Jalan Slamet Riyadi Di Surakarta - Prasetyo Febriarto (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
The purpose of this study is to get ideal conditions to create a comfortable pedestrian ways based thermal comfort microclimate. The method used is an experimental method through simulation using Envi-met software 3.1 with empirical measurements. Method to simulate existing conditions and ideal conditions. The results are used as a basis for referral arrangement pedestrian ways of the Slamet Riyadi space road. The results of this study stated that the thermal comfort on the pedestrian ways of the Slamet Riyadi road space in uncomfortable conditions (heat) and comfortable. Recommendations resulting from this study to organize pedestrian ways based micro climate thermal comfort based design of greenery